A Case of Daratumumab-Induced Significant Decrease in Donor-Specific HLA Antibodies and Remission Induction Before Haploidentical Stem Cell Transplantation in a Refractory B-ALL Patient. (October 2022) - Li, Xin; Zhu, Haibo; Sui, Tao; Zhao, Xingli; Deng, Qi
Objective: To explore the method of eliminating donor-specific anti-HLA antibodies (DSA) in haploidentical stem cell transplantation (haplo-SCT). Methods: We present a refractory B-cell acute lymphoblastic leukemia (ALL) patient who had strongly positive DSA, but had no human leukocyte antigen–matched donor. Although CD38 expression on leukemia cells was negative, daratumumab combined with etoposide and venetoclax therapy was chosen for her. Results: She achieved a significant decrease in DSA levels and complete remission on the combination therapy with daratumumab. She then received a haplo-SCT from a daughter as a donor and had a successful engraftment of donor stem cell. In haplo-SCT, strongly positive DSA levels, directed against donor HLA antigens, could be significantly reduced by daratumumab therapy before transplantation and successfully bridge subsequent haplo-SCT. Conclusion: Although CD38 expression is negative in leukemia cells, refractory B-ALL patients may still benefit from combination therapy with daratumumab. We need further clinical observation.